Role of Resistance Index in Differentiation of Benign and Malignant Breast Masses Compared with Histopathological Diagnosis - Amin, Mashah Binte; Yasmin, Tarana; Sarkar, Samar C; Rekha, Khaleda Parvin; Leeba, Rushaida Haque; Akhter, Nasima (Journal of Enam Medical College, 2019)
Background: Breast tumor remains a worldwide public health problem for women. Linear array sonography is currently one of the main diagnostic methods for detecting breast lumps. Duplex color Doppler sonography has been helpful to distinguish malignant from benign breast disease and also to predict the disease prognosis. Objectives: The purpose of this study was to evaluate the role of spectral Doppler as a method to measure the vascular resistance index in differential diagnosis between the benign and malignant breast neoplasm. Materials and Methods: This cross-sectional study was carried out in department of Radiology & Imaging of Enam Medical College & Hospital during January 2015 to December 2017. Sonography was done in 153 women having breast lumps. Among them histopathology was done in 105 cases. Ultrasonographic findings and histopathological report analyses were done using SPSS 13.0. Results: The study was done in 105 women with mean age 31.6 ± 4.5 years. On ultrasonogram, lesions were diagnosed as benign in 65 (62%) cases and malignant in 40 (38%) cases. Out of sonographically diagnosed 65 benign lesions having peripheral vascularity and decreased RI, 63 (97%) were proved benign histopathologically. With these criteria for diagnosis of benign lesion, sensitivity was 94%, specificity 92%, positive predictive value 95%, negative predictive value 89% and accuracy 93%. Sonographically 40 lesions were diagnosed as malignant. Among them 37 (92.5%) cases were proven malignant histopathologically and showed central vascularity and increased RI having sensitivity of 92%, specificity 94%, positive predictive value 89%, negative predictive value 95% and accuracy 93%. Conclusion: The analysis of vascular resistance index combined with findings on grayscale sonographic images correlates well with histopathological reports and can be of great assistance in the assessment of breast masses with high sensitivity and specificity. J Enam Med Col 2019; 9(2): 97-103